A new method for assessing the accuracy of full arch impressions in patients. (December 2016) - Kuhr, F.; Schmidt, A.; Rehmann, P.; Wöstmann, B.
Abstract: Objective: To evaluate a new method of measuring the real deviation (trueness) of full arch impressions intraorally and to investigate the trueness of digital full arch impressions in comparison to a conventional impression procedure in clinical use. Methods: Four metal spheres were fixed with composite using a metal application aid to the lower teeth of 50 test subjects as reference structures. One conventional impression (Impregum Penta Soft) with subsequent type-IV gypsum model casting (CI) and three different digital impressions were performed in the lower jaw of each test person with the following intraoral scanners: Sirona CEREC Omnicam (OC), 3 M True Definition (TD), Heraeus Cara TRIOS (cT). The digital and conventional (gypsum) models were analyzed relative to the spheres. Linear distance and angle measurements between the spheres, as well as digital superimpositions of the spheres with the reference data set were executed. Results: With regard to the distance measurements, CI showed the smallest deviations followed by intraoral scanners TD, cT and OC. A digital superimposition procedure yielded the same order for the outcomes: CI (15 ± 4 μm), TD (23 ± 9 μm), cT (37 ± 14 μm), OC (214 ± 38 μm). Angle measurements revealed the smallest deviation for TD (0.06° ± 0, 07°) followed by CI (0.07° ± 0.07°), cT (0.13° ± 0.15°) and OC (0.28° ± 0.21°). Conclusion: The new measuring method is suitable for measuring the dimensional accuracy of full arch impressions intraorally. CI is still significantly more accurate than full arch scans with intraoral scanners in clinical use. Clinical significance: Conventional full arch impressions with polyether impression materials are still more accurate than full arch digital impressions. Digital impression systems using powder application and active wavefront sampling technology achieve the most accurate results in comparison to other intraoral scanning systems (DRKS-ID: DRKS00009360, German Clinical Trials Register).